2011
DOI: 10.1097/ncn.0b013e31822b8a8f
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses and the Electronic Medical Record

Abstract: The advent of the electronic medical record has brought a new challenge to nursing education. Although most nursing students are proficient in data entry and computer skills, they often do not comprehend how the information they enter becomes a vital component of interdisciplinary team communication. Furthermore, the electronic medical record becomes a repository for information that can be retrieved for the purpose of decision support. Developed by the Cleveland Clinic, the Deans' Roundtable, and University H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Research suggests that integrating simulated EHRs in prelicensure nursing education is beneficial to students’ learning and development of important educational outcomes [ 20 , 30 , 34 ]. Simulated EHRs help improve students’ critical thinking [ 18 ] and their ability to navigate EHRs and understand informatics concepts such as data management [ 19 , 39 , 40 ]. Other researchers found that simulated EHRs help enhance students’ skills in electronic documentation [ 24 , 41 , 42 ] and aid in the development of positive attitudes and perspectives about electronic records [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that integrating simulated EHRs in prelicensure nursing education is beneficial to students’ learning and development of important educational outcomes [ 20 , 30 , 34 ]. Simulated EHRs help improve students’ critical thinking [ 18 ] and their ability to navigate EHRs and understand informatics concepts such as data management [ 19 , 39 , 40 ]. Other researchers found that simulated EHRs help enhance students’ skills in electronic documentation [ 24 , 41 , 42 ] and aid in the development of positive attitudes and perspectives about electronic records [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…reason, international studies have recommended that each university have an AeMR program for undergraduate nursing students to practice in accessing and entering data, using meaningful real-life scenarios scaffolded over the three-year program in a safe simulated environment. 7,21,22 The study findings revealed student's level of concern about developing a relationship with a patient whilst using a computer at the bedside. The international literature has identified that electronic documentation at the bedside can be a barrier for nurses in providing person-centred care, building positive nurse-patient relationships, [23][24][25] and effective patient communication.…”
Section: Discussionmentioning
confidence: 93%
“…Teknoloji ve sağlık alanındaki gelişmeler, teknoloji ve sağlık sektörünü birbirine daha bağımlı hale getirmiştir. Artık sağlık kurumlarında, hastalara ait bilgiler, manuel yöntemle doldurulan formlar ve dosyalar yerine, elektronik ortama aktarılarak ETK sistemi ile kullanılmaya başlanmıştır (7).…”
Section: Introductionunclassified